Antropomorfisme: Geliat Komunikasi Non-Human dan Pembentukan Citra Diri Manusia di Ranah Industri Animasi - Mudjiyanto, Bambang; Launa, Launa; Lusianawati, Hayu (FISIP Universitas Bung Karno, 2024)
AbstractThis study reviews the use of anthropomorphic techniques in the animation industry. Through qualitative research techniques based on descriptive-interpretive analysis, phenomenological approach, and the theory of anthropomorphism from Wells and Parkinson, this study reveals that the use of anthropomorphized animals in animation series and digital feature films mostly retains the natural characteristics and behavior of animals; only the characteristics and behavior of animal characters are represented/visualized in human form. The products of the animation industry make an important contribution to the reformulation of imagination and the formation of a positive human self-image, as the appeal of the story content is related to actual issues of human life. The use of anthropomorphic principles in the animation industry is not only entertaining, but conveys messages and high moral values and creates an emotional bond between the audience and the characters. In fact, anthropomorphism is a key element that has brought high-value stories and moral messages to audiences in the current era of the entertainment industry. This study encourages animation producers and creative film products to continue creating entertainment industry content that is relevant to the increasingly complex demands of audiences.Keyword: Antropomorphism, self-image formulation, media industry, animated product